2003
DOI: 10.1046/j.1365-2427.2003.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

A mixing model analysis of stream solute dynamics and the contribution of a hyporheic zone to ecosystem function*

Abstract: SUMMARY 1. We monitored streamwater and streambed sediment porewaters from White Clay Creek (WCC), SE Pennsylvania, for dissolved organic carbon (DOC), dissolved oxygen (DO) and conductivity to investigate organic matter processing within the hyporheic zone. Dissolved organic carbon and DO concentrations were higher in the streamwater than in the porewaters and, in many cases, concentrations continued to diminish with increasing depth into the streambed. 2. Hydrological exchange data demonstrated that the perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 56 publications
(86 reference statements)
10
119
0
Order By: Relevance
“…Exchange between the water column and channel bed and river banks (vertical and lateral linkages) can affect water quality because these are biogeochemically active areas where organic matter decomposition and nitrogen removal occurs [50,51]. Our results showed that water chemistry was not influenced by the restoration, and is in agreement with previous studies [52,53].…”
Section: Discussionsupporting
confidence: 92%
“…Exchange between the water column and channel bed and river banks (vertical and lateral linkages) can affect water quality because these are biogeochemically active areas where organic matter decomposition and nitrogen removal occurs [50,51]. Our results showed that water chemistry was not influenced by the restoration, and is in agreement with previous studies [52,53].…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between DOC concentration and the community structure of the epilithic, but not the sediment, community suggests that sources of organic carbon supporting secondary productivity partition differently between these two streambed habitats (42,54,56). While the epilithic populations are generally limited to dissolved carbon in the bulk flow and endogenous carbon (DOC and POC derived from the biofilm), the sediment populations likely obtain additional resources from entrained POC and DOC upwelling from the hyporheic zone (5,10,30,54). The appearance of both prokaryotic and eukaryotic primary producers in the epilithon during the summer months suggests a seasonal shift towards autocthonous carbon sources within this biofilm, as is also supported by prior estimates of autochthonous primary productivity in White Clay Creek (31).…”
Section: Discussionmentioning
confidence: 99%
“…Habitat differences in organic resources and sheer stress exist as well. For example, high depositional loads of POC and upwelling hyporheic zone DOC tend to be associated with sediment habitats (5,54), whereas algal biomass and associated exudates are more consistently present within rock-associated epilithic biofilms (30,31). Varying flows alter the sediment system through erosion and transport, redistributing the attached bacteria and likely exposing them to different environmental conditions.…”
mentioning
confidence: 99%
“…The purpose of field-based tracer studies is to gain a better understanding of stream solute transport behavior by accounting for transient storage zones. Previous transient storage studies have focused on relating transient storage to the following hydromorphic parameters: channel order and confinement (D'Angelo et al, 1993;Gabriel and Boufadel, 2002); streambed and aquifer lithology (substrate) (Valett et al, 1996Morrice et al, 1997;Argerich et al, 2011); discharge (Hall et al, 2002;Harvey et al, 2003); transient storage area (Mulholland et al, 1997;Laenen and Bencala, 2001;Gücker and Boëchat, 2004;Ensign and Doyle, 2005); channel bed form (Harvey and Bencala, 1993;Gooseff et al, 2003;Anderson et al, 2005;Wörman et al, 2007;Cardenas et al, 2008); wood debris, leaf packs, and vegetation (Gabriel and Boufadel, 2002;Wondzell et al, 2009b); streambed friction factor Salehin et al, 2003;Zarnetske et al, 2007); stream power per unit width (Zarnetske et al, 2007); channel tortuosity (Kasahara and Wondzell, 2003;Baker et al, 2012); and hyporheic exchange (as determined by hydraulic gradients and streambed-aquifer hydraulic conductivity) (Harvey et al, 1996;Battin et al, 2003;Wondzell et al, 2009a,b).…”
Section: T R Jackson Et Al: a Fluid-mechanics Based Classificationmentioning
confidence: 99%